2021
DOI: 10.3390/life11010052
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord: Information Mine in Sex-Specific Medicine

Abstract: Biological differences between sexes should be considered in all stages of research, as sexual dimorphism starts in utero leading to sex-specific fetal programming. In numerous biomedical fields, there is still a lack of stratification by sex despite primary cultured cells retaining memory of the sex and of the donor. The sex of donors in biological research must be known because variations in cells and cellular components can be used as endpoints, biomarkers and/or targets of pharmacological studies. This sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 147 publications
1
8
0
Order By: Relevance
“…In static culture, endothelial cells have been shown to display sexual dimorphism for a range of functions including proliferation, vasoregulation, migration, and wound healing, tube formation and vascular endothelial growth factor stimulation, response to stressors of hyperoxia and serum starvation, secreted factors, and stimulation by sex hormones. [41,42,44,45,46,[48][49][50][72][73][74][75][76][77] Our main effect results for cell spreading agree with reports on the characteristics of male and female rat aortic and microvascular endothelial cells that found female endothelial cells spread more than male endothelial cells. [46] It is important to note that this has immediate implications in terms of barrier function and wound healing ability, i.e., being able to cover a given area.…”
Section: Discussionsupporting
confidence: 91%
“…In static culture, endothelial cells have been shown to display sexual dimorphism for a range of functions including proliferation, vasoregulation, migration, and wound healing, tube formation and vascular endothelial growth factor stimulation, response to stressors of hyperoxia and serum starvation, secreted factors, and stimulation by sex hormones. [41,42,44,45,46,[48][49][50][72][73][74][75][76][77] Our main effect results for cell spreading agree with reports on the characteristics of male and female rat aortic and microvascular endothelial cells that found female endothelial cells spread more than male endothelial cells. [46] It is important to note that this has immediate implications in terms of barrier function and wound healing ability, i.e., being able to cover a given area.…”
Section: Discussionsupporting
confidence: 91%
“…We also reported that the association between the umbilical serum level of mercury and DNA methylation of umbilical cord tissue was different between both sexes 45 . Male and female offspring show several differences in their blood and tissues 46 . Recently, it was reported that the effects of gut microbiota on metabolism or gene expression were different between males and females in mouse models 47–49 .…”
Section: Discussionmentioning
confidence: 91%
“…Both the mother and the father contribute to the neonates’ genetic makeup; the quality of the fetal environment participates in the trajectory of fetus development [ 156 , 157 , 158 ]. Numerous maternal risk factors are identified, but paternal factors receive less attention [ 159 ].…”
Section: Factors That Can Affect the Pharmacological Responsementioning
confidence: 99%